2016
DOI: 10.1007/s11104-016-2851-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertilization on diazotrophic activity of microorganisms associated with Sphagnum magellanicum

Abstract: Background and aims In pristine ombrotrophic Sphagnum-dominated peatland ecosystems nitrogen (N) is often a limiting nutrient, which is replenished by biological N 2 fixation and atmospheric N deposition. It is, however, unclear which impact long-term N deposition has on microbial N 2 fixing activity and diazotrophic diversity, and whether phosphorus (P) modulates the response. Therefore, we studied the impact of increased N deposition and N depletion on microbial N 2 fixation and diazotrophic diversity associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 61 publications
5
41
0
Order By: Relevance
“…There are a number of potential explanations. First, the N inputs used here were based upon levels of N deposition recorded in the study area (∼3 kg N ha −1 year −1 ), and while these amounts are more realistic for our area and are in line with many newer studies that use smaller inputs (Gilliam et al ., ; Kox et al ., ; Tulloss and Cadenasso, ), the inputs are much lower than the levels of enrichment often used in nutrient limitation studies and in areas of exceptional deposition, such as some parts of Europe (Holland et al ., ). Second, as with most N deposition experiments, we applied the N in pulses that joined smaller daily rates into a compound amount, in our case applied twice yearly.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of potential explanations. First, the N inputs used here were based upon levels of N deposition recorded in the study area (∼3 kg N ha −1 year −1 ), and while these amounts are more realistic for our area and are in line with many newer studies that use smaller inputs (Gilliam et al ., ; Kox et al ., ; Tulloss and Cadenasso, ), the inputs are much lower than the levels of enrichment often used in nutrient limitation studies and in areas of exceptional deposition, such as some parts of Europe (Holland et al ., ). Second, as with most N deposition experiments, we applied the N in pulses that joined smaller daily rates into a compound amount, in our case applied twice yearly.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen fixation activity and temperature were negatively correlated which may be due to plant-specific tolerance to water stress and desiccation given that nitrogen fixation associated with moss is influenced by moisture (Zielke et al , 2002; Sorensen et al , 2006; Sorensen & Michelsen, 2011). Additionally, oxygen level, photosynthetic activity (Warren et al , 2017), and phosphorous (Rousk et al , 2017) or nitrogen availability (Kox et al , 2016) have also been found to limit diazotrophy in Sphagnum (Warren et al , 2017). However, we observed a reduction in diazotroph absolute abundance indicating diazotrophs were not inactive but rather undetectable with our methods in elevated temperature treatments.…”
Section: Discussionmentioning
confidence: 99%
“…N 2 fixing microorganisms (diazotrophs) live on the surface and inside dead hyaline cells of Sphagnum (Opelt et al, 2007;Bragina et al, 2012;Larmola et al, 2014), forming a symbiosis with their host. A highly diverse microbial community, including Proteobacteria, Verrucomicrobia and Cyanobacteria, has been found to colonize peat mosses (Bragina et al, 2014), and many of these microorganisms have the capacity to fix N 2 (Bragina et al, 2013;Kox et al, 2016). Also, in other bryophytes, like Hylocomiaceae (feather mosses), such a symbiotic relationship can be found with N 2 fixing cyanobacteria, supplying up to 50 % of the total N input in boreal forests (Rousk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%